Trauma-informed Education Viewed Through A Social Justice Lens: Introduction to the Special Issue - Gary Walsh; Michael S. Kelly (International Journal of School Social Work, 2021)
The purpose of this special issue is to apply a social justice lens to the question of how education practitioners operating within primary and secondary school contexts around the world are thinking about trauma-informed education and care. Papers explore what school social workers and other educators are doing to address these issues in schools and consider the broader implications of a global shift towards trauma-informed approaches in education. This special issue, the first one for IJSSW, features 10 papers from diverse fields (social work, psychology, education) that all reflect on how trauma-informed practices in schools can be enhanced and understood through the lens of social justice frameworks, and how this can inform further practice and research. This issue, published in October 2021, contains the first five articles. Issue 2 will be published in December, 2021, and contain the next five articles.
Keywords: trauma; teacher-student relationships; school mental health; school social work; social justice; trauma-informed care